Strategy for developing MSMES in Rejowinangun: digital marketing socialization and financial management (Case study all MSMEs in Kampung Gedong Kuning, DI Yogyakarta) (Strategi Pengembangan UMKM di Rejowinangun: Sosialisasi Pemasaran Digital dan Pengelolaan Keuangan (Studi Kasus Seluruh UMKM di Kampung Gedong Kuning DI Yogyakarta)) - Alisyah, Salsabiela Nuru; Selsabela, Adelia Ageng Yumna; Alfaizal, Muhammad Hasby; Safitri, Wahyu Fita; Rafhika, Aufha; Robbani, Tsabit Aqdam; Watulfa, Dwi Chintia; Bestari, Pretty; Khoirunnisa, Widiatri; Baihaki, Abdillah; Faishal, Muhammad (Indonesia Berdaya, 2025)
Many Micro, Small, and Medium Enterprises (MSMEs) face challenges due to incomplete and inaccurate information. The issue is difficulties in planning and providing targeted assistance to RW 2 Rejowinangun. Most MSME owners are not familiar with digital technology and have difficulties in making financial reports. It is necessary to introduce digital marketing and financial reports to reach a wider market and optimize business performance based on accurate financial data. Digital marketing is a marketing strategy that uses digital media and the internet. Meanwhile, financial statements are documents that record and summarize all financial transactions that occur in MSMEs. The method used is in the form of a survey by collecting data on the MSME database and socialization which is carried out by involving the PKK and MSMEs in RW 2 Rejowinangun. Suggestions from the results of the activities that have been carried out are to conduct regular training related to financial literacy and the use of easily accessible financial recording technology as well as training on the use of social media and the creation of marketing content. In addition, the development of an organized MSME database must be continuously updated to make it easier for the government and stakeholders to provide support. Abstrak. Banyak Usaha Mikro Kecil Menengah (UMKM) yang menghadapi tantangan akibat informasi yang tidak lengkap dan tidak akurat. Permasalahan tersebut adalah kesulitan dalam melakukan perencanaan dan pemberian bantuan yang tepat sasaran kepada RW 2 Rejowinangun. Sebagian besar pelaku UMKM belum mengenal teknologi digital dan kesulitan dalam membuat laporan keuangan. Perlu adanya pemasaran digital dan laporan keuangan untuk menjangkau pasar yang lebih luas serta mengoptimalkan kinerja usaha yang berbasis pada data keuangan yang akurat. Pemasaran digital merupakan strategi pemasaran yang memanfaatkan media digital dan internet. Sedangkan laporan keuangan merupakan dokumen yang mencatat dan merangkum seluruh transaksi keuangan yang terjadi pada UMKM. Metode yang digunakan berupa survei dengan melakukan pendataan pada database UMKM dan sosialisasi yang dilakukan dengan melibatkan PKK dan UMKM di RW 2 Rejowinangun. Saran dari hasil kegiatan yang telah dilakukan adalah melakukan pelatihan secara berkala terkait literasi keuangan dan pemanfaatan teknologi pencatatan keuangan yang mudah diakses serta pelatihan pemanfaatan media sosial dan pembuatan konten pemasaran. Selain itu, pengembangan basis data UMKM yang terorganisasi harus terus dimutakhirkan agar memudahkan pemerintah dan pemangku kepentingan dalam memberikan dukungan.